Repurposing Synthetic Congeners of a Natural Product Aurone Unveils a Lead Antitumor Agent Inhibiting Folded P-Loop Conformation of MET Receptor Tyrosine Kinase - Ahmed H. E. Hassan; Cai Yi Wang; Cheol Jung Lee; Hye Rim Jeon; Yeonwoo Choi; Suyeon Moon; Chae Hyeon Lee; Yeon Ju Kim; Soo Bin Cho; Kazem Mahmoud; Selwan M. El-Sayed; Sang Kook Lee; et al. (Pharmaceuticals, 2023)
A library of 24 congeners of the natural product sulfuretin were evaluated against nine panels representing nine cancer diseases. While sulfuretin elicited very weak activities at 10 µM concentration, congener 1t was identified as a potential compound triggering growth inhibition of diverse cell lines. Mechanistic studies in HCT116 colon cancer cells revealed that congener 1t dose-dependently increased levels of cleaved-caspases 8 and 9 and cleaved-PARP, while it concentration-dependently decreased levels of CDK4, CDK6, Cdc25A, and Cyclin D and E resulting in induction of cell cycle arrest and apoptosis in colon cancer HCT116 cells. Mechanistic study also presented MET receptor tyrosine kinase as the molecular target mediating the anticancer activity of compound 1t in HCT116 cells. In silico study predicted folded p-loop conformation as the form of MET receptor tyrosine kinase responsible for binding of compound 1t. Together, the current study presents compound 1t as an interesting anticancer lead for further development.